Analysis of “old” proteins unmasks dynamic gradient of cartilage turnover in human limbs - Hsueh, Ming-Feng (Sci Adv, 2019)
Unlike highly regenerative animals, such as axolotls, humans are believed to be unable to counteract cumulative damage, such as repetitive joint use and injury that lead to the breakdown of cartilage and the development of osteoarthritis. Turnover of insoluble collagen has been suggested to be very limited in human adult cartilage. The goal of this study was to explore protein turnover in articular cartilage from human lower limb joints. Analyzing molecular clocks in the form of nonenzymatically deamidated proteins, we unmasked a position-dependent gradient (distal high, proximal low) of protein turnover, indicative of a gradient of tissue anabolism reflecting innate tissue repair capacity in human lower limb cartilages that is associated with expression of limb-regenerative microRNAs. This association shows a potential link to a capacity, albeit limited, for regeneration that might be exploited to enhance joint repair and establish a basis for human limb regeneration.